Respuesta :
[tex]\bf a^2+b^2-(2ab)cos(C)=c^2\implies a^2+b^2-c^2=(2ab)cos(C)[/tex]
Since you have not provided the diagram, I cannot give a precise answer. However, I'll tell you how to solve this question.
We are given that:
a² + b² - 2abcosC = c²
We want to solve for 2abcosC. This means that we want to isolate the 2abcosC on one side of the equation.
We can do this as follows:
a² + b² - 2abcosC + 2abcosC = c² + 2abcosC
a² + b² - c² = c² + 2abcosC - c²
2abcosC = a² + b² - c²
Now in the diagram you have:
c is the side opposite to angle C
a is the side opposite to angle A
b is the side opposite to angle B
Plug in the values in the above equation, and you will simply have your answer.
Hope this helps :)
We are given that:
a² + b² - 2abcosC = c²
We want to solve for 2abcosC. This means that we want to isolate the 2abcosC on one side of the equation.
We can do this as follows:
a² + b² - 2abcosC + 2abcosC = c² + 2abcosC
a² + b² - c² = c² + 2abcosC - c²
2abcosC = a² + b² - c²
Now in the diagram you have:
c is the side opposite to angle C
a is the side opposite to angle A
b is the side opposite to angle B
Plug in the values in the above equation, and you will simply have your answer.
Hope this helps :)